Tingkat Pengetahuan Perawat dan Pelayanan Syariah Dalam Bidang Keperawatan di Rumah Sakit Islam Sultan Agung Semarang - Galuh Adityani; Muh Abdurrouf; Dyah Wiji Puspita Sari (Poltekkes Kemenkes Mataram, 2020)
ABSTRAKGaluh Adityani HUBUNGAN TINGKAT PENGETAHUAN PERAWAT DENGAN PELAYANAN SYARIAH DALAM BIDANG KEPERAWATAN DI RUMAH SAKIT ISLAM SULTAN AGUNG SEMARANG 58 halaman + 14 tabel + 2 gambar + 16 lampiran + xviii Latar Belakang: Pelayanan Syariah di bidang keperawatan merupakan pelayanan keperawatan yang terdiri dari standar pelayanan minimal rumah sakit syariah berupa hijab untuk pasien, pemasangan EKG sesuai gender, pemakaian hijab bagi ibu menyusui dan indikator mutu wajib syariah yaitu pemasangan kateter sesuai gender, dimana pelayanan Syariah tersebut merupakan pelayanan yang diharapkan oleh pasien. Tujuan penelitian ini untuk mengidentifikasi adakah hubungan antara tingkat pengetahuan perawat dengan pelayanan syariah di RSISA Semarang Metode: Penelitian ini menggunakan jenis penelitian kuantitatif dengan pendekatan cross sectional. Pengumpulan data menggunakan kuesioner dengan jumlah responden sebanyak 96. Penelitian ini menggunakan teknik simple random sampling dan diolah secara statistik dengan menggunakan korelasi spearmen. Hasil: Dari data karakteristik responden dalam penelitian ini dengan jumlah 96 responden 40,6% responden berumur 26-35 tahun, 66,7% responden berjenis kelamin perempuan, 62,5% responden berstatus sudah menikah, 60,4% responden pendidikan terakhir DIII, dan 56,3% responden lama kerja 1-5 tahun.Simpulan: Ada hubungan tingkat pengetahuan perawat dengan pelayanan syariah dalam bidang keperawatan di Rumah Sakit Islam Sultan Agung Semarang nilai p value 0,000 (p value <0,05 dan keeratan hubungan yaitu kuat (0,711) serta arah hubungannya positif Kata Kunci : Pelayanan Syariah Dalam Bidang keperawatan, Tingkat PengetahuanDaftrar Pustaka : 40 (2002-2017) NURSING SCIENCE STUDY PROGRAMFACULTY OF NURSING SCIENCEISLAMIC UNIVERSITY OF SULTAN AGUNG SEMARANGThesis, January 2020 ABSTRACTGaluh Adityani THE RELATIONSHIP BETWEEN THE LEVEL OF KNOWLEDGE OF NURSES AND ISLAMIC SERVICES ON NURSING AT SULTAN AGUNG ISLAMIC HOSPITAL SEMARANG58 pages + 14 tables + 2 pictures + 16 appendices + xviii Background: Islamic services on nursing is the nursing services performed by nurses based on the quran and the hadist, which include indicators of the minimum service standard and quality indicators of compulsory shariah, between other reading basmalah in administering drugs and action, the hijab for patients, the ECG installation of appropriate gender, reminiscent of the time of prayer, the DC installation of appropriate gender. The purpose of this research is to identify the relationship between the level of knowledge of nurses and Islamic services on nursing at sultan agung Islamic hospital semarangMathod: This study used quantitative method with cross sectional approach. The data collection used observation. The total of respondents was 96 nurses with simple random sampling. The data analysis used Spearman test.Results: Research shows that islamic services are good as many as 62 respondents (98.4%), indicating that islamic services are sufficient 1 respondent (1.6%) and which shows less than 0 respondents (0.0%) islamicservices. At the level of knowledge of nurses with sufficient categories that showed good Islamic services as many as 13 respondents (68.4%), showed enough Islamic services 5 respondents (26.3%) and who showed less Islamic services as much as 1 respondent (5.3%). While the level of knowledge of nurses with less categories that indicate good Islamic services as many as 2 respondents (14.3%), which shows enough Islamic services as many as 2 respondents (14.3%) and who show less Islamic services as many as 10 respondents (71.4% ).Conclusion: There is a significant the relationship between the level of knowledge of nurses and Islamic services on nursing at sultan agung Islamic hospital semarang with p-value 0.000 (p-value<0.05) and the closeness of the relationship was moderate (0.711) as well as the direction of the relationship was positive Keyword : Islamic services on nursing, level knowledgeBibliography : 40 (1989 – 2017)